Reindeer carcasses provide foraging habitat for insectivorous birds of the alpine tundra - Badia, Rudy; Steyaert, Sam; Puliti, Stefano; Blaalid, Rakel; Frank, Shane (Ornis Norvegica, 2019)
On August of 2016, almost an entire herd (n = 323) of wild tundra reindeer (Rangifer tarandus) was killed by lightning on Hardangervidda in southern Norway. While conducting fieldwork for another study in 2017, we opportunistically registered the occurrence and behaviour of birds on carcasses from this mass die-off. Several passerine species other than corvids were observed actively foraging on arthropods, such as blowfly (Calliphoridae sp.) adults and larvae, which are typically associated with carcass decomposition. We quantified observations of those birds, and described their foraging behaviour at the carcass site. In decreasing order of abundance, five passerine species were observed taking arthropods at the site: Meadow Pipit (Anthus pratensis), Northern Wheatear (Oenanthe oenanthe), Common Reed Bunting (Emberiza schoeniclus), Bluethroat (Luscinia svecica,), and Lapland Bunting (Calcarius lapponicus). Systematic surveys of passerines utilizing carcass sites would further our understanding of how such resources may affect behaviour and life history of various bird species. publishedVersion